EFFECTIVENESS OF COOPERATIVE LEARNING AND CONCEPTUAL CHANGESTRATEGIES IN IMPROVING LEARNING OUTCOMES OFPROSPECTIVE TEACHERS WITH DIFFERENT RELIGIOUS INCLINATION - Delphonso, Bamidel Tokunbo (PEOPLE: International Journal of Social Sciences, 2018)
The study examined the Effectiveness of Cooperative Learning and Conceptual Change Strategies in improving Learning Outcomes of College of Education Biology Students. The study adopted a non-equivalent pre-test, post-test control group design. The study population comprised Part III Biology Education students in colleges of education in Southwestern Nigeria. Two instruments were used to collect data for the study. The first instrument is ATE and retention test. The second instrument is AQE. The data collected were analysed using ANOVA and ANCOVA).The results indicated that the CLS was more effective in improving the performance of Biology education students with Christian, Islamic and traditional religious belief systems more than the CCS, there was a significant difference between the CLS group pre-test and CLS group post-test (Mean difference = 18.14, p = 0.000). Also, there was a significant difference in the CCS group pre-test and post-test (Mean difference = 10.155, p = 0.000). Moreover, there was also a slight significant difference in the TEM pre-test and post-test scores (mean difference = 6.500, p = 0.036). Therefore, the hypothesis was rejected. However, if the mean difference between the pretest and the posttest in the three groups were compared, the CLS group has the highest (18.14), CCS group was 10.15, while the TEM group has the lowest (6.500).Moreover, when the means of the groups were compared, the CLS group has the highest mean score (58.02) and the CCS group mean score was 52.05. This is an indication that the CLS group has more positive effect on performance of students in evolution. However, the result indicated that there was a significant difference in the attitude of students in the CLS and CCS groups before and after treatments. This implies that the two strategies (Cooperative Learning Strategy and Conceptual Change Strategy) caused the students to have a change of attitude towards the concept of evolution and most importantly their religious inclination no longer distorts scientific facts.